Inquiry-driven essay assessment (IDEA) as a framework for evaluating students’ argumentation in static fluids - Suminar, Iin; Nurdini, Nurdini; Fratiwi, Nuzulira Janeusse; Abdurrahaman, Dudung; Purwanto, Muhammad Guntur (Universitas Islam Negeri Raden Intan Lampung, 2025)
Argumentation is a fundamental aspect of scientific literacy, enabling students to construct, justify, and evaluate claims based on evidence. However, traditional assessments emphasize rote memorization rather than developing reasoning skills, highlighting the need for a more effective evaluation approach. This study aims to develop and validate the Inquiry-Driven Essay Assessment (IDEA) framework to assess students' argumentation skills in static fluids. The research employs the ADDIE model. The participants comprised 26 eleventh-grade students from a Bandung, West Java private school who had prior knowledge of static fluid concepts, including hydrostatic pressure, buoyant force, and the principles of floating and sinking objects. The findings indicate that the developed assessment instrument demonstrates high validity and reliability, with strong internal consistency and alignment with learning objectives. The claim generation aspect obtained the highest average score, while the evidence analysis, justification, and support aspects require further improvement. The study concludes that the IDEA framework can serve as an effective tool for assessing and enhancing students' argumentation skills. The implications of this research suggest that implementing the IDEA framework can provide a more comprehensive and objective evaluation approach in science education, thereby assisting educators in fostering students' critical thinking and argumentation skills more effectively.